Description of Panagrellus ulmi sp. n. (Rhabditida, Panagrolaimidae) from Iran, and comments on the species of the genus and its relatives - Abolafia, Joaquín; Alizadeh, Mehrdad; Khakvar, Reza (Zootaxa, 2016)
A new species of the genus Panagrellus, P. ulmi sp. n., has been found inside wetwood cankers of elms from the city of Tabriz, Iran. The new species is characterized by having small body size (0.91‒1.22 mm long in females and 0.82‒1.18 mm long in males), lateral field with three longitudinal incisures, lip region narrowing to distal end with six small lips and oral opening surrounded by six acute liplets, stoma with gymnostom shorter than cheilostom, cheilorhabdia not refringent, gymnorhabdia refringent, pharynx with metacorpus not swollen and isthmus slender, excretory pore at level of metacorpus, ovary very long without flexures, oviduct swollen, postvulval uterine sac long, 2.0‒3.4 times the corresponding body diameter, both female and male tails conoid-elongate, spicules with rounded and ventrally bent manubrium and lamina with dorsal anterior hump and fork-like bifurcate tip, gubernaculum with anterior dorsal handle-like manubrium, postcloacal genital papillae five pairs, two anterior subventral, one anterior subdorsal at same level than the first subventral, one posterior subventral and one posterior subdorsal both at same level. Description, measurements and illustrations are provided. In addition, species of Panagrellus and its relatives (Panagrobelus and Plectonchus) are analyzed. After this analysis, Plectonchus hunti is considered an intermediate species between Panagrellus and Panagrobelus, and is transferred, based on morphological and molecular evidence, to the latter genus as Panagrobelus hunti n. comb. On the other hand, Panagrellus (Panagrellinae) and Baujardia (Baujardinae), are two very similar genera according to both morphological and molecular evidence; we consider the respective subfamilies synonyms. Also, Plectonchus and Anguilluloides show great similarities, which justify considering Anguilluloides a junior synonym of the former genus. A. procerus is accordingly transferred as Plectonchus procerus n. comb. while Anguilluloides zondagi is considered a new junior synonym of Plectonchus molgos. Finally, emended diagnoses of the genera Panagrellus, Panagrobelus and Plectonchus, compendia, and keys to their species identification are included.